Cellular distribution of activity for three enzymes with maltose binding protein as fusion partner and the structural implications - SARIYAR AKBULUT, BERNA (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2010)
The bacterial SEC pathway is commonly used for secretion of heterologous proteins in E. coli by fusing them to transported proteins to facilitate downstream processing. While some proteins are translocated very efficiently, some reside in the cytoplasm. In this work, maltose binding protein (MBP) was fused to 3 cytoplamic enzymes from Thermus thermophilus (serine protease, 251 residues; glucose isomerase, 381 residues; pullulanase, 718 residues) to study the protein transport from the cytoplasm by quantifying the distribution of activities in different cellular compartments. Pullulanase activity was harvested exclusively in the periplasm; however, glucose isomerase activity was harvested exclusively in the cytoplasm. Considerable serine protease activity was found in the periplasm, but after 10 h of induction activity dropped sharply and no activity was found thereafter in either compartment. This was attributed to the instability of the plasmid probably caused by the proteolytic activity of the protease Computations of hypothetical folding rates and secondary structure contents of the proteins showed that folding rates, in addition to alpha-helix and beta-sheet contents of proteins, could be important determinants for efficient translocation by the SEC pathway. These results may give clues to predict whether a protein would be a suitable fusion tail for periplasmic transport with MBP.
Keywords: MBP fusion protein; periplasmic secretion; protein length; secondary structure; folding rate; AMINO-ACID-SEQUENCE; ESCHERICHIA-COLI; FOLDING RATES; BETA-HAIRPIN; GLUCOSE-ISOMERASE; PREDICTION; TRANSLOCATION; EXPRESSION; MECHANISM; DYNAMICS